О Некоторых Аспектах Имущественных Правоотношений Ибадитов С Христианами = Sur certains aspects des relations de propriété des Ibadites avec les Chrétiens - Radivilov, Danylo (Восточная Европа в древности и средневековье: Экономические основы формирования государства в древности и средневековье : XXV Чтения памяти члена-корреспондента АН СССР В.Т. Пашуто и памяти чл.-кор. АН СССР А.П. Новосельцева Москва, 17-19 апреля 2013 г. Материалы конференции, 2013)

Экспедиция оманских ибадитов на Cокотру в хронике Тухфат ал-а‘йан би-сират ахл ‘уман = Expédition des Ibadites omanais à Socotra dans la Chronique de Tuhfat al-a’yan bi-sirat ahl 'uman - Radivilov, Danylo (XXVII Международная научная конференция по источниковедению и историографии стран Азии и Африки «Локальное наследие и глобальная перспектива», 2013)

المدرسة الجمنية: دراسة معمارية لنموذج من المعالم الرسمية بجبل مطماطة - بوخشيم, النوري (القيروان وجهتها: دراسات جديدة في الآثار والتراث. أعمال الندوة العلمية الدولية الثالثة لقسم علم الآثار (القيروان 1-4 أفريل 2009), 2013)

‏رهانات الديني السياسي في مدينة غرداية فضاء عمومي أو فضاء جماعاتي؟ - المستاري, جيلالي; نوار, فؤاد (Les espaces publics au Maghreb: au carrefour du politique, du religieux, de la société civile, des medias et des NTIC = ‏الفضاءات العمومية في البلدان المغاربية: لقاء السياسي، الديني، المجتمع المدني والتكنولوجيات الحديثة للإعلام والاتصال, 2013)

دور القواعد الفقهية في تطوير النظريات - التيواجني, مهني بن عمر (‏أعمال ندوة تطور العلوم الفقهية النظرية الفقهية والنظام الفقهي: ‏المنعقدة خلال عام 15-18 ‏جماد الأولى 1433هـ/7-10-4-2012م, 2013)

Homme à Si Jilani Bel Haj Yahya - Tmarzizet, Kamel (Séminaire Jilani Bel Haj Yahia - personnalités Djerbiennes (1ère édition) = ملتقى الجيلاني بالحاج يحيى لأعلام جربة (الدورة الأولى), 2013)
Keywords: Biographies -- Djerba -- 20e siècle

Un passionné de littérature - Younes, Ahmed (Séminaire Jilani Bel Haj Yahia - personnalités Djerbiennes (1ère édition) = ملتقى الجيلاني بالحاج يحيى لأعلام جربة (الدورة الأولى), 2013)
Keywords: Biographies; Biographies -- Djerba -- 20e siècle

جربة أجيم تحتفي بالباحث الجيلاني بن الحاج يحيى - قوجة, محمد (Séminaire Jilani Bel Haj Yahia - personnalités Djerbiennes (1ère édition) = ملتقى الجيلاني بالحاج يحيى لأعلام جربة (الدورة الأولى), 2013)

Tifidellas - Ben Maamar, Fathi (Ifsan n tamunt : tullisin n tmurt tmazga, 2013)
Keywords: Littérature -- Djerba

فقه التعايش عند الشيخ اطفيش من خلال كتابه "شرح النيل" - باجو, مصطفى بن صالح (أعمال ندوة تطور العلوم الفقهية: فقه رؤية العالم والعيش المشترك - المذاهب الفقهية والتجارب المعاصرة, 2013)
Keywords: Atfiyyash, Muhammad b. Yusuf (1821-1914)

The Rise of Tribal Politics - Pack, Jason; Larcher, Wolfram (The 2011 Libyan Uprisings and the Struggle for the Post-Qadhafi Future, 2013)
Keywords: Vie politique -- Djebel Nefousa

The Solitary Sultan and the Construction of the New Oman - Peterson, John E. (Governance in the Middle East and North Africa: a handbook, 2013)
Keywords: Vie politique -- Oman -- 1970-2020

L’habitat mozabite au M’Zab - Bousquet, Christian (Habitat, État, société au Maghreb, 2013)
Keywords: Urbanisme -- Mzab

The Bilād al-Maghrib: Rebels, Saints, and Heretics - Loimeier, Roman (Muslim societies in Africa: a historical anthropology, 2013)

“Regionalizing Oman”: A New Interest of Research on Oman and Its Spatial Dimensions - Wippel, Steffen (Regionalizing Oman: Political, Economic and Social Dynamics, 2013)

Concluding Remarks: Regionalizing Oman Beyond Conventional Metageographies - Wippel, Steffen (Regionalizing Oman: Political, Economic and Social Dynamics, 2013)

Bringing the Global and the Local Together Through English in Oman - Mahrooqi, Rahma Ibrahim al-; Tuzlukova, Victoria (Regionalizing Oman: Political, Economic and Social Dynamics, 2013)

The Political Economy of Internationalization and Privatization of Higher Education in the Sultanate of Oman - Brandenburg, Torsten (Regionalizing Oman: Political, Economic and Social Dynamics, 2013)

Musandam: Creating a New Region Across the Water - Dietl, Gulshan (Regionalizing Oman: Political, Economic and Social Dynamics, 2013)

Domesticating Local Elites. Sheikhs, Walis and State-Building Under Sultan Qaboos - Valeri, Marc (Regionalizing Oman: Political, Economic and Social Dynamics, 2013)
Keywords: Vie politique -- Oman -- 1970-2020

Private Documents as a Source for Regional History: The Archive of the ʿAbrīyīn of Al-Ḥamrāʾ - Hoffmann-Ruf, Michaela (Regionalizing Oman: Political, Economic and Social Dynamics, 2013)
Keywords: Archives -- Oman

The Impact of Shopping Malls on Traditional Retail Stores in Muscat. Case Study of Al-Seeb Wilayat - Abdelghani, Montasser I.M. (Regionalizing Oman: Political, Economic and Social Dynamics, 2013)
Keywords: Tourisme -- Oman

Is Littoralization Reconfiguring the Omani Territory? - Mokhtar, Belgacem (Regionalizing Oman: Political, Economic and Social Dynamics, 2013)
Keywords: Littoraux -- Djerba

Musandam and Its Trade with Iran. Regional Linkages Across the Strait of Hormuz - Benz, Michael (Regionalizing Oman: Political, Economic and Social Dynamics, 2013)

Oman Caught Between the GCC Customs Union and Bilateral Free Trade with the US: Is It Worth Breaking the Rules? - Zorob, Anja (Regionalizing Oman: Political, Economic and Social Dynamics, 2013)

Oman and the Indian Ocean Rim – Economic Integration Across Conventional Meta-Regions - Wippel, Steffen (Regionalizing Oman: Political, Economic and Social Dynamics, 2013)

Re-reading the Role of Oman Within Its International Trade Relations: From the Sixteenth Through to the Nineteenth Centuries - Nicolini, Beatrice (Regionalizing Oman: Political, Economic and Social Dynamics, 2013)

Negotiating Authenticity and Translocality in Oman: The “Desertscapes” of the Harasiis Tribe - Chatty, Dawn (Regionalizing Oman: Political, Economic and Social Dynamics, 2013)

Oman-India Relations: Exploring the Long-Term Migration Dynamics - Pradhan, Samir (Regionalizing Oman: Political, Economic and Social Dynamics, 2013)

Of Red Cells, Translocality and Origins: Inherited Blood Disorders in Oman - Beaudevin, Claire (Regionalizing Oman: Political, Economic and Social Dynamics, 2013)
Keywords: Biologie -- Oman

“We Are Part of Zanzibar” – Translocal Practices and Imaginative Geographies in Contemporary Oman-Zanzibar Relations - Verne, Julia; Müller-Mahn, Detlef (Regionalizing Oman: Political, Economic and Social Dynamics, 2013)
Keywords: Relations -- Oman -- Afrique de l'Est

The Baluch presence in the Persian Gulf - Peterson, John E. (Sectarian Politics in the Persian Gulf, 2013)
Keywords: Vie politique -- Oman -- 1970-2020

Star charts of Oman - Nash, Harriet; Agius, Dionisius A. (Sources and approaches across disciplines in Near Eastern studies: proceedings of the 24th congress, Union Européenne des Arabisants et Islamisants, Leipzig 2008, 2013)
An overview of the Falaj systems and timing of water shares, followed by an explanation of the provenance of the only three documents related to the practice of star gazing found (all from the 20th century) and a discussion of their application and significance.
Keywords: Navigation -- Oman

Riḥlat Sulaymān Bāshā al-Bārūnī al-ʿIlmiyya ilà Maʿhad al-Quṭb wa-Atharuhā fī Takwīnihi ‘l-Fikrī wa’l-ʿIlmī - Wāsmāʿīl, Zuhayr (al-Nadwa al-Duwaliyya: Sulaymān Bāshā al-Bārūnī wa-Ḥuḍūruhu fī ‘l-Thaqāfa al-ʿUmāniyya, 10-11 Yūlyū 2012. Buḥūth al-Nadwa, 2013)
Keywords: Bārūnī, Sulaymān al- (1870-1940)

al-Bārūnī Mufakkiran wa-Muṣliḥan - Wā’ilī, Saʿīd b. Sulaymān al- (al-Nadwa al-Duwaliyya: Sulaymān Bāshā al-Bārūnī wa-Ḥuḍūruhu fī ‘l-Thaqāfa al-ʿUmāniyya, 10-11 Yūlyū 2012. Buḥūth al-Nadwa, 2013)
Keywords: Bārūnī, Sulaymān al- (1870-1940)

Sulaymān Bāshā al-Bārūnī: ʿAlāqatuhu bi-A’immat ʿUmān wa-Salāṭīnihā wa-Juhūduhu ‘l-Fikriyya wa’l-Iṣlāḥiyya - ʿUbaydī, Sālim b. Hāshil al- (al-Nadwa al-Duwaliyya: Sulaymān Bāshā al-Bārūnī wa-Ḥuḍūruhu fī ‘l-Thaqāfa al-ʿUmāniyya, 10-11 Yūlyū 2012. Buḥūth al-Nadwa, 2013)
Keywords: Bārūnī, Sulaymān al- (1870-1940)

al-Marḥala al-ʿUmāniyya fī Ḥayāt al-Bārūnī bi-Dākhiliyyat ʿUmān - Shuʿaylī, Muḥammad b. Sulaymān al- (al-Nadwa al-Duwaliyya: Sulaymān Bāshā al-Bārūnī wa-Ḥuḍūruhu fī ‘l-Thaqāfa al-ʿUmāniyya, 10-11 Yūlyū 2012. Buḥūth al-Nadwa, 2013)
Keywords: Bārūnī, Sulaymān al- (1870-1940)

al-Marḥala al-ʿUmāniyya fī Ḥayāt al-Shaykh Sulaymān al-Bārūnī (1924-1940) - Ṣawwāfī, ʿAlī Ḥamza al- (al-Nadwa al-Duwaliyya: Sulaymān Bāshā al-Bārūnī wa-Ḥuḍūruhu fī ‘l-Thaqāfa al-ʿUmāniyya, 10-11 Yūlyū 2012. Buḥūth al-Nadwa, 2013)
Keywords: Bārūnī, Sulaymān al- (1870-1940)

Ḥuḍūr Sulaymān al-Bārūnī fī ‘l-Ṣiḥāfa al-Iṣlāḥiyya al-Jazā’iriyya (1920-1940) - Qawbaʿ, ʿAbd al-Qādir (al-Nadwa al-Duwaliyya: Sulaymān Bāshā al-Bārūnī wa-Ḥuḍūruhu fī ‘l-Thaqāfa al-ʿUmāniyya, 10-11 Yūlyū 2012. Buḥūth al-Nadwa, 2013)
Keywords: Bārūnī, Sulaymān al- (1870-1940)

Riḥlāt al-Bārūnī wa-Ahdāfuhā - Nāʿibī, Sulṭān b. Khamīs b. ʿĪsà al- (al-Nadwa al-Duwaliyya: Sulaymān Bāshā al-Bārūnī wa-Ḥuḍūruhu fī ‘l-Thaqāfa al-ʿUmāniyya, 10-11 Yūlyū 2012. Buḥūth al-Nadwa, 2013)
Keywords: Bārūnī, Sulaymān al- (1870-1940)

Riḥlāt al-Bārūnī wa-Atharuhā fī ‘l-Taghyīr al-Ijtimāʿī li-Ḥayāt al-Shuʿūb - Karrūm, Aḥmad Ḥammū (al-Nadwa al-Duwaliyya: Sulaymān Bāshā al-Bārūnī wa-Ḥuḍūruhu fī ‘l-Thaqāfa al-ʿUmāniyya, 10-11 Yūlyū 2012. Buḥūth al-Nadwa, 2013)
Keywords: Bārūnī, Sulaymān al- (1870-1940)

Ṣilāt Sulaymān al-Bārūnī al-Niḍāliyya maʿa Salṭanat ʿUmān khilāl al-Ghazw al-Īṭālī li-Lībiyā - Jabārāt, Maḥmūd Muḥammad al- (al-Nadwa al-Duwaliyya: Sulaymān Bāshā al-Bārūnī wa-Ḥuḍūruhu fī ‘l-Thaqāfa al-ʿUmāniyya, 10-11 Yūlyū 2012. Buḥūth al-Nadwa, 2013)
Keywords: Bārūnī, Sulaymān al- (1870-1940)

Ḥuḍūr al-Shaykh Sulaymān Bāshā al-Bārūnī fī ‘l-Thaqāfa al-ʿUmāniyya: Adabiyyāt Ziyāratihi li-Baldat al-Ḥamrā’... Namūdhajan - ʿIbrī, ʿAlī b. Hilāl al- (al-Nadwa al-Duwaliyya: Sulaymān Bāshā al-Bārūnī wa-Ḥuḍūruhu fī ‘l-Thaqāfa al-ʿUmāniyya, 10-11 Yūlyū 2012. Buḥūth al-Nadwa, 2013)
Keywords: Bārūnī, Sulaymān al- (1870-1940)

Sulaymān Bāshā al-Bārūnī Murabbiyan wa-Muṣliḥan - Ibn Saʿdūn, al-Munīr ʿAbd al-Ḥamīd (al-Nadwa al-Duwaliyya: Sulaymān Bāshā al-Bārūnī wa-Ḥuḍūruhu fī ‘l-Thaqāfa al-ʿUmāniyya, 10-11 Yūlyū 2012. Buḥūth al-Nadwa, 2013)
Keywords: Bārūnī, Sulaymān al- (1870-1940)

Ṣūrat al-Bārūnī fī Shiʿr Abī Salām al-Kindī - Siyābī, Aḥmad b. Saʿūd al- (al-Nadwa al-Duwaliyya: Sulaymān Bāshā al-Bārūnī wa-Ḥuḍūruhu fī ‘l-Thaqāfa al-ʿUmāniyya, 10-11 Yūlyū 2012. Buḥūth al-Nadwa, 2013)
Keywords: Bārūnī, Sulaymān al- (1870-1940)

Malāmiḥ Shakhṣiyyat Sulaymān al-Bārūnī Bāshā min khilāl Majallat al-Minhāj - Yaṭṭū, ʿĀ’isha (al-Nadwa al-Duwaliyya: Sulaymān Bāshā al-Bārūnī wa-Ḥuḍūruhu fī ‘l-Thaqāfa al-ʿUmāniyya, 10-11 Yūlyū 2012. Buḥūth al-Nadwa, 2013)
Keywords: Bārūnī, Sulaymān al- (1870-1940)

Difāʿ al-Mujāhid Sulaymān Bāshā al-Bārūnī ʿan Ḥudūd Lībiyā min khilāl al-Lā’iḥa allatī qaddamahā ilà Ra’īs al-Wuzarā’ al-ʿUthmānī Sanat 1910 - Zarrīqī, Jumʿa Maḥmūd al- (al-Nadwa al-Duwaliyya: Sulaymān Bāshā al-Bārūnī wa-Ḥuḍūruhu fī ‘l-Thaqāfa al-ʿUmāniyya, 10-11 Yūlyū 2012. Buḥūth al-Nadwa, 2013)
Keywords: Bārūnī, Sulaymān al- (1870-1940)

Sulaymān Bāshā al-Bārūnī: Nashāṭuhu ‘l-ʿIlmī wa-Niḍāluhu ‘l-Siyāsī - Zurmān, Aḥmad; Ḥaqāyin, Jumʿa (al-Nadwa al-Duwaliyya: Sulaymān Bāshā al-Bārūnī wa-Ḥuḍūruhu fī ‘l-Thaqāfa al-ʿUmāniyya, 10-11 Yūlyū 2012. Buḥūth al-Nadwa, 2013)
Keywords: Bārūnī, Sulaymān al- (1870-1940)

al-Bārūnī wa’l-Jazā’ir fī Ẓill al-Iḥtilāl al-Faransī - Saʿd Allāh, Abū ‘l-Qāsim (al-Nadwa al-Duwaliyya: Sulaymān Bāshā al-Bārūnī wa-Ḥuḍūruhu fī ‘l-Thaqāfa al-ʿUmāniyya, 10-11 Yūlyū 2012. Buḥūth al-Nadwa, 2013)
Keywords: Bārūnī, Sulaymān al- (1870-1940)

Sulaymān Bāshā al-Bārūnī wa-Nashāṭuhu ‘l-Siyāsī fī ‘l-Mahjar (1924-1940) - Qanāwī, Arwīʿī Muḥammad ʿAlī (al-Nadwa al-Duwaliyya: Sulaymān Bāshā al-Bārūnī wa-Ḥuḍūruhu fī ‘l-Thaqāfa al-ʿUmāniyya, 10-11 Yūlyū 2012. Buḥūth al-Nadwa, 2013)
Keywords: Bārūnī, Sulaymān al- (1870-1940)

Sulaymān Bāshā al-Bārūnī al-Shāʿir al-Faqīh - Qaffa, Qāsim Ḥasan al- (al-Nadwa al-Duwaliyya: Sulaymān Bāshā al-Bārūnī wa-Ḥuḍūruhu fī ‘l-Thaqāfa al-ʿUmāniyya, 10-11 Yūlyū 2012. Buḥūth al-Nadwa, 2013)
Keywords: Bārūnī, Sulaymān al- (1870-1940)

al-Marjaʿiyyāt al-Thaqāfiyya fī Shiʿr al-Bārūnī - Muḥāsana, Muḥammad (al-Nadwa al-Duwaliyya: Sulaymān Bāshā al-Bārūnī wa-Ḥuḍūruhu fī ‘l-Thaqāfa al-ʿUmāniyya, 10-11 Yūlyū 2012. Buḥūth al-Nadwa, 2013)
Keywords: Bārūnī, Sulaymān al- (1870-1940)

Sulaymān al-Bārūnī Adīban wa-Mu’arrikhan - Kuḥḥūlī, Zuhra Saʿdallāwī Ḥaram (al-Nadwa al-Duwaliyya: Sulaymān Bāshā al-Bārūnī wa-Ḥuḍūruhu fī ‘l-Thaqāfa al-ʿUmāniyya, 10-11 Yūlyū 2012. Buḥūth al-Nadwa, 2013)
Keywords: Bārūnī, Sulaymān al- (1870-1940)

al-Rathā’ fī Shiʿr Sulaymān Bāshā al-Bārūnī - Jarrār, ʿAbd al-Rāziq Fāliḥ (al-Nadwa al-Duwaliyya: Sulaymān Bāshā al-Bārūnī wa-Ḥuḍūruhu fī ‘l-Thaqāfa al-ʿUmāniyya, 10-11 Yūlyū 2012. Buḥūth al-Nadwa, 2013)
Keywords: Bārūnī, Sulaymān al- (1870-1940)

al-Su’āl wa-Dalālatuhu fī Shiʿr Sulaymān al-Bārūnī (Dirāsa fī ‘l-Adawāt) - Hindī, ʿAlī al- (al-Nadwa al-Duwaliyya: Sulaymān Bāshā al-Bārūnī wa-Ḥuḍūruhu fī ‘l-Thaqāfa al-ʿUmāniyya, 10-11 Yūlyū 2012. Buḥūth al-Nadwa, 2013)
Keywords: Bārūnī, Sulaymān al- (1870-1940)

al-Dawr al-Siyāsī li’l-Shaykh al-Bārūnī min khilāl Majlis al-Maʿbūthān - Hāzil, ʿAlī ʿUmar al- (al-Nadwa al-Duwaliyya: Sulaymān Bāshā al-Bārūnī wa-Ḥuḍūruhu fī ‘l-Thaqāfa al-ʿUmāniyya, 10-11 Yūlyū 2012. Buḥūth al-Nadwa, 2013)
Keywords: Bārūnī, Sulaymān al- (1870-1940)

Ḥuḍūr al-Bārūnī fī ‘l-Shiʿr al-ʿUmānī bayna Ṣūrat al-Mujāhid wa-Shakhṣiyyat al-Muṣliḥ - Ḥajarī, Muḥammad b. Saʿīd b. ʿĀmir al- (al-Nadwa al-Duwaliyya: Sulaymān Bāshā al-Bārūnī wa-Ḥuḍūruhu fī ‘l-Thaqāfa al-ʿUmāniyya, 10-11 Yūlyū 2012. Buḥūth al-Nadwa, 2013)
Keywords: Bārūnī, Sulaymān al- (1870-1940)

Mawqif Īṭāliyā min Anshiṭat Sulaymān al-Bārūnī, 1914-1924 - Ghawīṭa, Miftāḥ Balʿīd (al-Nadwa al-Duwaliyya: Sulaymān Bāshā al-Bārūnī wa-Ḥuḍūruhu fī ‘l-Thaqāfa al-ʿUmāniyya, 10-11 Yūlyū 2012. Buḥūth al-Nadwa, 2013)
Keywords: Bārūnī, Sulaymān al- (1870-1940)

Khilāf Sulaymān Bāshā al-Bārūnī maʿa ‘l-Amīr Shakīb Arslān wa-Mawqif al-Shaykh ʿAbd al-Ḥamīd b. Bādīs minhu - Fāyd, Bashīr (al-Nadwa al-Duwaliyya: Sulaymān Bāshā al-Bārūnī wa-Ḥuḍūruhu fī ‘l-Thaqāfa al-ʿUmāniyya, 10-11 Yūlyū 2012. Buḥūth al-Nadwa, 2013)
Keywords: Bārūnī, Sulaymān al- (1870-1940)

Mawāqif al-Bārūnī fī ‘l-Aḥdāth al-Maḥalliyya wa’l-ʿĀlamiyya bi-Baghdād, 1931-1937 - Bahjat, Mujāhid Muṣṭafà; Ṣaqrī, Saʿīd b. ʿAbd Allāh b. Sallām al- (al-Nadwa al-Duwaliyya: Sulaymān Bāshā al-Bārūnī wa-Ḥuḍūruhu fī ‘l-Thaqāfa al-ʿUmāniyya, 10-11 Yūlyū 2012. Buḥūth al-Nadwa, 2013)
Keywords: Bārūnī, Sulaymān al- (1870-1940)

Dawr al-Shaykh Sulaymān al-Bārūnī fī Muwājahat al-Istiʿmār al-Īṭālī - ʿĀshūrī, Qamʿūn (al-Nadwa al-Duwaliyya: Sulaymān Bāshā al-Bārūnī wa-Ḥuḍūruhu fī ‘l-Thaqāfa al-ʿUmāniyya, 10-11 Yūlyū 2012. Buḥūth al-Nadwa, 2013)
Keywords: Bārūnī, Sulaymān al- (1870-1940)

Mawqif al-ʿĀlim al-Mujāhid Sulaymān al-Bārūnī min Mas’alat Ilghā’ al-Khilāfa al-ʿUthmāniyya ʿĀm 1924 M., - ʿĀlim, ʿIzz al-Dīn ʿAbd al-Salām al- (al-Nadwa al-Duwaliyya: Sulaymān Bāshā al-Bārūnī wa-Ḥuḍūruhu fī ‘l-Thaqāfa al-ʿUmāniyya, 10-11 Yūlyū 2012. Buḥūth al-Nadwa, 2013)
Keywords: Bārūnī, Sulaymān al- (1870-1940)

al-Abʿād al-Fikriyya wa’l-Falsafiyya wa’l-Adabiyya fī Kitābāt Sulaymān al-Bārūnī - Abū ʿAlūsh, Ibrāhīm Muḥammad; Ḥarāḥasha, Aḥmad al- (al-Nadwa al-Duwaliyya: Sulaymān Bāshā al-Bārūnī wa-Ḥuḍūruhu fī ‘l-Thaqāfa al-ʿUmāniyya, 10-11 Yūlyū 2012. Buḥūth al-Nadwa, 2013)
Keywords: Bārūnī, Sulaymān al- (1870-1940)

Sulaymān al-Bārūnī: Dawruhu fī Maydān al-Jihād wa-Ta’sīs al-Jumhūriyya al-Ṭarāblusiyya (1873-1940) - ʿAbd, Aḥmad Ḥusayn; ʿAlī, Munà Jalāl (al-Nadwa al-Duwaliyya: Sulaymān Bāshā al-Bārūnī wa-Ḥuḍūruhu fī ‘l-Thaqāfa al-ʿUmāniyya, 10-11 Yūlyū 2012. Buḥūth al-Nadwa, 2013)
Keywords: Bārūnī, Sulaymān al- (1870-1940)

موقف الفرق الإسلامية من الخليفة عثمان بن عفان رضي الله عنه - شبيب, نايف محمد (بحوث الندوة العلمية: ذو النورين عثمان بن عفان رضي الله عنه صحبة صادقة وخلافة راشدة, 2013)
من المعلوم لدى الباحثين في التاريخ الإسلامي أن فتنة مقتل الخليفة الراشدي الثالث عثمان بن عفان رضي الله عنه سنة: عنه 35 ه كانت أعظم فتنة تصيب المسلمين بعد وفاة الرسول صلى الله عليه وسلم، إذ كانت مدة خلافته اثنا عشرة سنة، وعلى الرغم من أنه من المبشرين بالجبنة والأحاديث التي وردت في فضله كثيرة جدا، إلا أن هناك من المسلمين من رأى فيه رأيا آخر، ولا سيما بعض الفرق الإسلامية التي تذبذب موقفها منه رضي الله عنه، فالبعض لم يرض بخلافته كلها، والبعض كفره، والبعض قسم خلافته قسمين، رضي عنه في القسم الأول (ست سنوات) ولم يرض عنه في القسم الثاني السنوات الست الأخرى، وفي هذه الورقة سوف نسلط الضوء على موقف هذه الفرق ( الخوارج، الشيعة، المعتزلة، المرجئة...) من هذا الخليفة الراشدي، ومن ثم بيان سبب هذه المواقف والرد عليها وتفنيدها.

نظرة حول نشأة و تطور مدينة تاهرت - بويحياوي, عز الدين (فعاليات الملتقى الدولي الثاني: العمران والعمارة في المتوسط خلال العهدين القديم والوسيط في ضوء المصادر الأثرية والأدبية, 2013)
Keywords: Urbanisme -- Tahert

التبديع والتكفير في الخطاب الاباضي الأصولي : الوارجلاني (ت 570هـ / 1175م) والخليلي انموذجاً - الجلاصي, بثينة (أشغال الندوة العلمية الدولية: المد المذهبي المعاصر, 2013)

Laylà bint Tarif's Rita' : An exemple of Kharijite Female Poetry - Masullo, Mariangela (Islam and globalisation: historical and contemporary perspectives: proceedings of the 25th Congress of L'Union Européenne des Arabisants et Islamisants, 2013)
Keywords: Kharijisme

A Political Culture and Foreign Policy Shaped by a Moderate Religious View: The Case of the Sultanate of Oman - Rabi, Uzi (Oman and overseas, 2013)
Keywords: Vie politique -- Oman -- 1970-2020

The South East European View - Ziaka, Angeliki (Oman and overseas, 2013)

Historical Coincidences between Oman and Brazil: Portuguese Invaders, African Slaves and the Majlis al-Jinn - Pacheco, Leila M. S. (Oman and overseas, 2013)
Keywords: Esclavage -- Oman

The Seminar für Orientalische Sprachen (SOS) at Berlin: Aspects of the Relationship between Oman and Germany in the Late 19th and Early 20th Century - Hoffmann-Ruf, Michaela (Oman and overseas, 2013)
Keywords: Relations -- Oman -- Allemagne

A Historical Survey of US-Omani Relations from 1790 to the Present - Leonard, Douglas R. (Oman and overseas, 2013)
Keywords: Relations -- Oman -- Etats-Unis

Oman through Jewish Travellers’ Eyes - Schreiner, Stefan (Oman and overseas, 2013)
Keywords: Judaïsme -- Oman; Récits de voyage -- Oman

Danish and Norwegian Travel Accounts of Oman, 1765–1995: Changing Views across Sea and Land - Bang, Anne K. (Oman and overseas, 2013)
Keywords: Récits de voyage -- Oman

African Perspectives - Kusimba, Chapurukha M. (Oman and overseas, 2013)

Mosaic Oman: Views from India - Dietl, Gulshan (Oman and overseas, 2013)

Zanzibar: The Sultanate and the Ottoman State in Africa - Gol, Mohammed Z. (Oman and overseas, 2013)

Oman: The Arab Views - Ghazal, Amal N. (Oman and overseas, 2013)

Oman: The Russian View since the 15th Century - Rezvan, Efim (Oman and overseas, 2013)
Keywords: Récits de voyage -- Oman

Oman and Ibadism in Modern French Historiography: Assessing a Semi-Failure - Dridi, Moez (Oman and overseas, 2013)

The British Historical View of Oman and Ibadism - Worrall, James (Oman and overseas, 2013)

Wood, Horses and Friendship. The Arabic Letters from Muscat to the Dutch in Kochi (1779) and Batavia (1798–1806) - Witkam, Jan Just (Oman and overseas, 2013)

Oman and Omanis in Portuguese Sources in the Early Modern Period (ca. 1500-1750) - Cunha, João Teles e (Oman and overseas, 2013)
Keywords: Relations -- Oman -- Portugal

Omani Trade and Cultural Relations with East Asian Countries - Ziaee, Ali Akbar (Oman and overseas, 2013)
Keywords: Commerce -- Oman

From Slumber to Assertion: Maritime Expansion of the Ibadis of Oman and the Responses of Estado da India,1622–1720 - Malekandathil, Pius (Oman and overseas, 2013)

The Formation of Oman’s Maritime Power under the Yaariba and Sayyid Said - Staples, Eric (Oman and overseas, 2013)

The Growth of the Relationships between Oman, the Gulf and the Western Waters of the Indian Ocean. Oman: The Corner-Stone of a Maritime System - Piacentini Fiorani, Valeria (Oman and overseas, 2013)

The Portuguese in East Africa and the Omani Reconquest of East Africa - Newitt, Malyn (Oman and overseas, 2013)
Keywords: Relations -- Oman -- Portugal

The Main Languages of East Africa and their Literatures - Bakari, Mohammed Ali (Oman and overseas, 2013)
Keywords: Littérature -- Zanzibar

Ibadis in East Africa: Archaeological and Historical Evidence - Horton, Mark (Oman and overseas, 2013)
Keywords: Archéologie -- Zanzibar

The Swahili Coast: Africa’s Window on the Indian Ocean - Sheriff, Abdul Mohamed Hussein (Oman and overseas, 2013)

Omani Seafaring and Omani Boat - Vosmer, Tom (Oman and overseas, 2013)
Keywords: Archéologie -- Oman

Umani Ports in Chinese Sources - Kauz, Ralph (Oman and overseas, 2013)

Omani Seafaring Identity before the Early 1600s: Ethnic and Linguistic Diversity - Agius, Dionisius A. (Oman and overseas, 2013)
Keywords: Navigation -- Oman

The Origins of Omani Identity - Wilkinson, John Craven (Oman and overseas, 2013)

Late pre-Islamic Oman: The Inner Evidence – The Outside View - Yule, Paul A. (Oman and overseas, 2013)
Keywords: Archéologie -- Oman

Les fortifications de l'île de Djerba : enjeux doctrinaux et stratégies méditerranéennes (Xe-XVIe siècles) - Hbaieb, Mohamed Ali (Fortificações e território na Península Ibérica e no Magreb: séculos VI a XVI, 2013)
Keywords: Bardawi, mosquée al- (Mezrane, Djerba); Monuments -- Djerba

Nourritures médiévales: L'alimentation au maghreb d'après les sources ibadites (xie-xiiie siècle) - Prevost, Virginie (Travelling through time: essays in honour of Kaj Öhrnberg, 2013)
Keywords: Alimentation -- Afrique du Nord

The Birds of Djerba - Torres-Recinos, Julio (Cloudburst: an anthology of Hispanic Canadian short stories, 2013)
Keywords: Littérature -- Djerba

Emblèmes territoriaux et attachement aux origines : le cas des communautés djerbienne et gafsienne à Morneg - Kdhai, Houda (Penser la société tunisienne aujourd'hui: la jeune recherche en sciences humaines et sociales, 2013)
Keywords: Emigration -- Djerba

Les articulations de l’Afrique Mineure dans le Périple dit de Scylax - Cheyns, André; Isebaert, Labert; Mund-Dopchie, Monique; Desanges, Jehan (Heureux qui comme Ulysse: hommage à Monique Mund-Dopchie, 2013)
Les recherches scientifiques du Monique Mund-Dopchie, à qui ce volume rend hommage, s'articulent autour de trois axes essentiels : la survie des tragiques grecs à la Renaissance; la représentation, dans l'imaginaire antique, des régions situées aux confins du monde; la réception des récits de voyage grecs et latins à l'époque des Grandes Découvertes. C'est cette dernière orientation que les éditeurs ont privilégiée en organisant un colloque sur le "Voyage dans l'Antiquité grecque", afin d'illustrer quelques-uns des thèmes majeurs qui traversent l'oeuvre scientifique du Pr Monique Mund- Dopchie: la découverte de l'inconnu, l'attrait du lointain et la rencontre de l'Autre. La première partie de cette publication réunit quatre communications portant, d'abord sur le Voyage, et plus particulièrement sur les errances d'Ulysse
Keywords: Archéologie -- Djerba

Arab-Berber contacts in the Middle Ages and ancient Arabic dialects: new evidence from an old Ibāḍite religious text - Brugnatelli, Vermondo (African Arabic: Approaches to Dialectology, 2013)
L’analyse d’un long manuscrit contenant un texte arabo-berbère du Moyen Âge, le Kitāb al- barbariyya, connu aussi sous le nom de Moudaououana d’Ibn R’anem (Motylinski et Bossoutrot) ou Mudawwana d’Abû Ġânim al-Ḫurâsânî (Ould-Braham et U-Madi), permet de relever quelques phénomènes liés au contact linguistique entre le berbère et l’arabe du Moyen Âge. La date de composition du texte n’est pas connue mais elle remonte à une époque assez reculée (entre le 10ème et le 15ème siècle). Plusieurs indices (entre autres, l’orthographe du son [g], transcrit avec <ǧ> et pas avec <q>) font penser à une période antérieure ou très proche de l’invasion hilalienne. Parmi les phénomènes observables, on notera : - d’un côté les emprunts du berbère à l’arabe, qui sont concentrés surtout dans le domaine de la religion, même si la langue du document préserve beaucoup de lexique indigène. Dans quelques cas, on peut constater une évolution dans l’utilisation des emprunts d’un livre à l’autre à l’intérieur de l’ouvrage, probablement en raison d’une différence d’époque de composition des différentes parties ; - de l’autre côté, dans certains cas, comme les noms de nombre de la deuxième dizaine, la forme de l’emprunt démontre une évolution déjà avancée de la langue arabe parlée au Maghreb par rapport à la langue « classique ».
Keywords: Linguistique -- Djebel Nefousa